Tumores cutâneos/subcutâneos localizados em região de mama e clinicamente diagnosticados como neoplasias mamárias em cães - Barraza, Vanessa Cirinéa Tapia (2021)
Canine skin tumors are relatively common in the mammary region. Due to their location, these tumors can occasionally be misdiagnosed as mammary neoplasms, which can lead to inadequate surgical approaches. The aim of this study was to investigate the prevalence of skin tumors with an erroneous suspicion of mammary neoplasms and submitted to a Veterinary Pathology Service. The biopsy archives from Laboratório de Patologia Veterinária (LPV) of the Universidade Federal de Santa Maria (UFSM) were searched (2010-2018) and canine skin tumors affecting the mammary region were selected. According to clinical information from hospital records and biopsy reports, these tumors were divided in three categories according to clinical suspicion at the time of surgery: (1) mammary neoplasm; (2) skin tumor; (3) undetermined. Additional epidemiologic and clinic information were collected from biopsy reports and hospital records from the patients attending to the Hospital Veterinário of UFSM. Cases suspected of mammary neoplasms and with available paraffin blocks were histologically reevaluated. Of 1,826 skin tumors with known location, 128 (7%) affected the mammary region. A pre- surgical cytologic analysis was preformed in 29 cases (29/128). In six of these, cytology helped ruling out a mammary neoplasm; in nine, the exam supported the initial suspicion of mammary neoplasm; and in 14, cytology did not change the initial suspicion. Among these 128 tumors, 69 (54%) had a mistaken suspicion of mammary neoplasm at the time of surgery, with or without the aid of cytology. The histopathologic diagnosis of these tumors varied from inflammatory and hyperplastic lesions to neoplastic changes. Lipomas (14/69), vascular tumors (10/69), follicular cysts (9/69), mast cell tumors (9/69) and squamous cell carcinomas (8/69) were the most frequent diagnoses. Fifty-four cases were histologically evaluated, however, tumor location within the skin was determined in only 30 cases, of which 21 were restricted to superficial and/or deep dermis. In five cases (three mast cell tumors, one lipoma and one squamous cell carcinoma) the tumor not only affected the subcutis but also infiltrated the mammary gland. The 69 tumors were divided in two categories: (1) those that were solitary, with no other tumors affecting the mammary area (47/69); (2) and those that accompanied one or more mammary neoplasms (22/69). The surgical approach was only analyzed in cases with solitary tumors, as the presence of other neoplasms could affect surgeon decisions. The 47 dogs with a solitary skin tumor in the mammary area were submitted to nodulectomy (30) or mastectomy (17). Five mastectomies were partial, eight were unilateral and four were bilateral. At least 12/47 (25.5%) of the cases, mastectomy was considered unnecessary. This study highlights the resemblance between mammary neoplasms and skin tumors affecting the mammary area in dogs, and reinforces how important is the clinical differentiation of this tumors. We believe this study will guide clinicians and surgeons, reducing the error rates in the future, and consequently contributing to improve the clinical and surgical management of these patients, which will ultimately improve their prognosis.